2014
DOI: 10.1007/s10048-014-0426-9
|View full text |Cite
|
Sign up to set email alerts
|

The LITAF/SIMPLE I92V sequence variant results in an earlier age of onset of CMT1A/HNPP diseases

Abstract: Charcot-Marie-Tooth disease type 1A (CMT1A) and hereditary neuropathy with liability to pressure palsies (HNPP) represent the most common heritable neuromuscular disorders. Molecular diagnostics of CMT1A/HNPP diseases confirm clinical diagnosis, but their value is limited to the clinical course and prognosis. However, no biomarkers of CMT1A/HNPP have been identified. We decided to explore if the LITAF/SIMPLE gene shared a functional link to the PMP22 gene, whose duplication or deletion results in CMT1A and HNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 24 publications
0
20
0
3
Order By: Relevance
“…Despite this genetic homogeneity of CMT1A, patients present with considerable clinical phenotypic variability . Existing studies had limited success in identifying genetic CMT1A modifiers …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this genetic homogeneity of CMT1A, patients present with considerable clinical phenotypic variability . Existing studies had limited success in identifying genetic CMT1A modifiers …”
Section: Discussionmentioning
confidence: 99%
“…These cases represent a rare cause of the severe phenotype in which the fourth copy of PMP22 further exaggerates the PMP22 dosage effect and contributes to disease severity. In addition, mutations in lipopolysaccharide‐induced TNF factor ( LITAF ), a gene known to cause demyelinating CMT, have been reported to contribute to a more severe phenotype and earlier onset in CMT1A . Recently, microRNA 149 ( MIR149 ) has been reported as a genetic modifier for disease onset and severity in a group of CMT1A patients with Asian ancestry .…”
mentioning
confidence: 99%
“…The highest age at onset was 73. While I92V LITAF (lipopolysaccharide‐induced tumor necrosis factor‐alpha factor) sequence variant resulted in earlier onset of HNPP, genotype related to elderly onset is not yet determined. Although several studies showed mild clinical presentation of HNPP with small deletion of PMP22 gene, elderly‐onset cases with the typical 1.5‐Mb deletion have been reported .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, no biological basis for clinical variability of CMT1A is known. However, a recent study of a large cohort of CMT1A/HNPP-affected patients conducted by Sinkiewicz-Darol et al (2015) determined that the LITAF I92V sequence variant predisposes patients to an earlier age of onset of CMT1A as well as hereditary neuropathy with liability to pressure palsies (HNPP) diseases. It is noteworthy that HNPP is characterized by a single copy of PMP22 (Chance et al 1993), but point mutations have also been reported (Nicholson et al 1994).…”
Section: Gene Dosage Effect Of Pmp22 In Cmt1a Diseasementioning
confidence: 99%